2011
DOI: 10.3324/haematol.2011.047894
|View full text |Cite
|
Sign up to set email alerts
|

High levels of CD34+CD38low/-CD123+ blasts are predictive of an adverse outcome in acute myeloid leukemia: a Groupe Ouest-Est des Leucemies Aigues et Maladies du Sang (GOELAMS) study

Abstract: The online version of this article has a Supplementary Appendix. BackgroundAcute myeloid leukemias arise from a rare population of leukemic cells, known as leukemic stem cells, which initiate the disease and contribute to frequent relapses. Although the phenotype of these cells remains unclear in most patients, these cells are enriched within the CD34 + CD38low/-compartment expressing the interleukin-3 alpha chain receptor, CD123. The aim of this study was to determine the prognostic value of the percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
129
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(144 citation statements)
references
References 27 publications
14
129
1
Order By: Relevance
“…CD123 is found in all AML subtypes (and interestingly on B lymphoblastic leukemias). In fact IL-3Rα overexpression on AML blasts was associated with poor prognosis features such as Flt3 ligand mutations, unfavorable karyotype, and failure to achieve remission (23). Fortuitously there is often aberrant overexpression of CD123 on CD34+CD38-AML cells.…”
Section: Antibody Designmentioning
confidence: 99%
“…CD123 is found in all AML subtypes (and interestingly on B lymphoblastic leukemias). In fact IL-3Rα overexpression on AML blasts was associated with poor prognosis features such as Flt3 ligand mutations, unfavorable karyotype, and failure to achieve remission (23). Fortuitously there is often aberrant overexpression of CD123 on CD34+CD38-AML cells.…”
Section: Antibody Designmentioning
confidence: 99%
“…The concept of the leukaemic stem cell (LSC) is well established in AML and the frequency of the CD34 + CD38 − stem cell compartment with aberrant marker expression has proven predictive of adverse outcome in several studies (Vergez et al , 2011; Terwijn et al , 2014). Following the seminal studies by Bakker et al (2004), we have identified the C‐type lectin domain family 12, member A (CLEC12A) (also named hMICL and CLL‐1) as a stable and reliable leukaemia‐associated marker at diagnosis and as a tool for assessing minimal residual disease in AML (Larsen et al , 2012; Roug et al , 2014).…”
mentioning
confidence: 99%
“…For most patients with CD34-positive AML, the relapse-relevant AML-LSCs are contained predominantly in the compartments of CD34-positive and (CD34-positive CD38-negative) cells. 12,40,4346,73 Therefore, we have first enriched CD34-bearing cells from 2 patients with CD34-positive AML, for whom sufficient cell numbers were available (patients 9 & 11; Table 3), by immuno-magnetic sorting with a commercial kit. Both samples carried intermediate combined densities of CD33 plus CD123 on their blasts (MNCs; approx.…”
Section: Resultsmentioning
confidence: 99%